THE REDEFINITION OF PUBLIC SPACE BY YOUNG SPORTSPERSONS - THE SOCIAL NATURE OF THE IMAGINARY WORLD OF STREET SKATEBOARDING AND LE PARKOUR (Fiep Bulletin - online, 2014)
Abstract: The practice of adventure and risk sports, such as surfing, biking, skating, skateboarding and recently in Brazil parkour, originates from a spectacular revolution, from the logic of adaptation to an age of dizzying exchanges. Street skateboarding and Parkour are treated here as urban-adventure practices, where these young enthusiasts, during their leisure hours, imprint their acts with true, challenging meanings, overcoming barriers and possible prejudices of the society imposed upon them. The study has two objectives: (a) to investigate the meaning of adventure, risk and vertigo in the urban environment - factors which appear in the conversations of street skaters and parkour enthusiasts - and (b) to place in evidence the symbolic elements that emerge in these conversations. The procedure used was the interpretive, qualitative, ethnographic approach and analysis of the conversations transmitted in the sayings of street skating and le parkour enthusiasts.  Street skaters and traceurs de parkour present in the urban setting were interviewed. The preliminary analyses indicate that these young street skaters and traceurs de parkour weave new paths, design their own routes and infringe the street ordinances established for cities. To these youths, the city is not limited to specific forms of bourgeois spatial use; it evokes vibrant practices with a route plan idealized by the youths.
Keywords: adventure; risk; vertigo; street skateboarding; parkour